The 3T model of military veteran radicalization and extremism: exploring risk factors and protective strategies - Hazel R. Atuel; Carl A. Castro (Frontiers in Sociology)
In the aftermath of several wars within the last century, seminal research forewarned against the rising tide of radicalization and violent extremism (VE) among military veterans. Building on the pioneering work, the current study explores risk and protective factors related to military veteran extremism. Utilizing the retrospective thick description approach, the study utilized both primary (e.g., interviews) and open-source (e.g., court transcripts) data to examine and contextualize the VE trajectory across the military lifecycle (premilitary, military, postmilitary), as informed by people from various social networks (e.g., family, civilian/premilitary). The select sample comprised 30 VE veterans and 30 VE civilians who committed/planned a VE act between 2003 and 2019, and a comparison group of 10 non-VE veterans (i.e., veterans who resisted radicalization and VE). Directed content analyses results yielded a conceptual model reflecting three general risk factors (Transmission of Prejudice, Trauma and Adversity, and Transition) common among civilian and veterans alike. In addition, behavioral and cognitive strategies related to three general protective strategies (Resistance against Transmission of Prejudice, Addressing Trauma and Overcoming Adversity, Navigating Transitions) were found to steer veterans away from radicalization and VE across the military lifecycle. Implications for future research are discussed.